Understanding Nature Sports Organizations in Portugal - Melo, Ricardo J. E. S. de (2016)
Although Nature Sports are considered a growing phenomenon around the world, there is a lack of research and data about the organizations that are developing these activities. The purpose of this paper is to characterize the Nature Sports Organizations operating in mainland Portugal. Data was obtained through an online survey questionnaire applied to organizations which promoted Nature Sports in Portugal, both from private and public sectors, and 166 answers were obtained. Three main types of organizations were found based on their legal form and organizational vocation: sport tourism companies, sport clubs, and associations (environmentalists, cultural, sportive, recreational and others) which were further characterized by their organization profile, supply and demand. The results show significant statistical differences between the different types of organizations regarding their age, number of collaborators, and type of activities offered, as also the number and provenience of the practitioners. The data also enclose implications for the Nature Sports policies and Nature Sports Organizations management that will be discussed.